2010
DOI: 10.1111/j.1574-695x.2010.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusbiofilm formation and tolerance to antibiotics in response to oscillatory shear stresses of physiological levels

Abstract: Bacterial infections in the blood system are usually associated with blood flow oscillation generated by some cardiovascular pathologies and insertion of indwelling devices. The influence of hydrodynamically induced shear stress fluctuations on the Staphylococcus aureus biofilm morphology and tolerance to antibiotics was investigated. Fluctuating shear stresses of physiologically relevant levels were generated in wells of a six-well microdish agitated by an orbital shaker. Numerical simulations were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Furthermore, in response to varied levels of fluid flux, variations on the staphylococcal cell have been investigated using flow chambers to determine changes in the presence of microbial surface components recognizing adhesive matrix molecules, MSCRAMMs, which are involved in the ability of S. aureus to colonize (53). These investigations demonstrated that the S. aureus MSCRAMMs function in a shear-dependent manner, whereby the binding efficiency to host factors peaks under conditions of low fluid shear (50,54).Previous investigations have also demonstrated the ability of S. aureus to sense and respond to fluid shear flux by altering biofilm architecture (31,63). Specifically, studies of indwelling medical devices have indicated that S. aureus is an efficient biofilm former under various degrees of fluid shear (31, 63).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, in response to varied levels of fluid flux, variations on the staphylococcal cell have been investigated using flow chambers to determine changes in the presence of microbial surface components recognizing adhesive matrix molecules, MSCRAMMs, which are involved in the ability of S. aureus to colonize (53). These investigations demonstrated that the S. aureus MSCRAMMs function in a shear-dependent manner, whereby the binding efficiency to host factors peaks under conditions of low fluid shear (50,54).Previous investigations have also demonstrated the ability of S. aureus to sense and respond to fluid shear flux by altering biofilm architecture (31,63). Specifically, studies of indwelling medical devices have indicated that S. aureus is an efficient biofilm former under various degrees of fluid shear (31, 63).…”
mentioning
confidence: 97%
“…Previous investigations have also demonstrated the ability of S. aureus to sense and respond to fluid shear flux by altering biofilm architecture (31,63). Specifically, studies of indwelling medical devices have indicated that S. aureus is an efficient biofilm former under various degrees of fluid shear (31,63).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The oscillating flow behavior arising in 6-well plates can represent the physiological flows observed in vivo. Both increased shear stress levels and flow oscillation associated with plate motion were observed to contribute to biofilms formation (Kostenko et al, 2010). …”
Section: Free Surface Flow and Wall Shear Stress Analysis In Agitatedmentioning
confidence: 99%